Warisan mahawangsa Kedah - Mahani Musa; Ahmad Jelani Halimi; Persatuan Sejarah Malaysia. Cawangan Kedah (Alor Setar, Kedah : Persatuan Sejarah Malaysia, Cawangan Kedah, 2006)
Historical, sociopolitical, and economic aspects of Kedah from 17th to 20th century; collection of articles
Bibliografi : p. 184-192
In Malay
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Kedah -- History